Pengaruh Teamwork Dan Disiplin Kerja Terhadap Produktivitas Kerja Pegawai Pada Dinas Perindustrian Dan Perdagangan Kabupaten Bima - Muh. Bahtiar; Kartin Aprianti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of teamwork and work discipline on the work productivity of employees at the Department of Industry and Trade of Bima Regency. The approach used in this research is using an associative approach. The sample in this study was 45 respondents. The data collection techniques used were observation, questionnaires, and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, t tests, and F tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results showed that teamwork (X1) and work discipline (X2) simultaneously have a significant effect on employee work productivity at the Bima Regency Industry and Trade Service with an effect of 53.2%.